PROSES PERENCANAAN PARTISIPATIF DALAM REHABILITASI DAN REKONSTRUKSI PERMUKIMAN PASCABENCANA MERAPI 2010 Studi Kasus: Desa Wukirsari dan Desa Candibinangun Kabupaten Sleman - , MARIA A. RADJI SILI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Basically, the process of participative planning always involves the community inside, therefore at this stage the community does not only has a role as object, but furthermore as the subject/actor of an activity. Bottom up planning through participative pattern has recently been applied, however there are only a small number of cases involved with the process of participative planning itself. In fact, this kind of process of participative planning happens in Merapi's surronding (especially in Wukirsari and Candibinangun villages) in the rehabilitation and reconstruction of residences surrounding Merapi after erruption, in a program called Rekompak, a recent post-disaster participative process for Merapi inhabitants and the \"speciality\" of this participative process. The objective of this research is to describe the process of participative planning in the rehabilitation and reconstruction of the surrounding residences after the erruption of merapi in Wukirsari and Candibinangun villages. Furthermore, to identify factors that affect community participation in rehabilitation and reconstruction of the residences after the erruption of Merapi in 2010. This research uses case study method and the applied analysis are individual case analysis and cross-case analysis. Data is collected through observation, documentation, and in-depth interview with the local people as informans who are directly involved in the activities of rehabilitation and reconstruction of residences after the erruption and well understand about the program. This research indicates that both the factor of participative planning and the process of participative planning that involve the participation of the community in the implementation of post-disater rehabilitation and reconstruction activites, are distinguished based on the severity level that creates the differences of level of personal interest within the community. When the level of severity is considered high, it can be reflected by the interest of each individual within a community and not the representative of individual interest, thus the process of participative planning will be more detail. Beside that, the factors that affect the participative planning will be lesser and more simple. Only rural area with the community social character of harmonious, high level of tolerance, caring, and togetherness that is able to apply the process of participative planning in terms of post-disaster rehabilitation and reconstruction.